Membangun kepemimpinan profetik santri: Kontribusi OSTADA di Pesantren Daarul Uluum Lido - Firdaus, Ghobi Ghilman; Sa'diyah, Maemunah; Subagiya, Bahrum (Program Studi Magister Pendidikan Agama Islam, 2023)
Leaders in organizations play a significant role in guiding, motivating, and shaping the organization's direction. The leadership style held by the leader can have a significant impact on his followers. Leadership based on wisdom, gentleness, and courage is the hallmark of Prophetic leadership upheld in Islam. As a great leader, Prophet Muhammad SAW practised leadership that combines strength and gentleness in carrying out his duties. This study explores the Organization of Santri Tahfizh Daarul Uluum Lido (OSTADA) 's role in improving students' prophetic leadership attitude at Pesantren Tahfizh Daarul Uluum Lido. This research uses a qualitative approach with data collection through observation, interviews, and documentation. The data were analyzed by considering primary and secondary data. The results showed that OSTADA is a formal organization that helps organize santri activities in the pesantren. They apply a leadership concept that reflects the exemplary attitude of the Prophet Muhammad SAW, namely